2016
DOI: 10.1108/ijopm-01-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

Why be first if it doesn’t pay? The case of early adopters of C-TPAT supply chain security certification

Abstract: Purpose The purpose of this paper is to focus on adoption of certified management standards, specifically public standards. Such standards play an increasingly important role in today’s business environment. However, to generate adoption benefits, they must be first widely accepted – a situation where they have become viewed as the de facto norms. For this state to occur early adopters play a critical role. Past research has argued that early adopters, in exchange for assuming more risk, are rewarded with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 58 publications
(143 reference statements)
0
34
1
Order By: Relevance
“…However, given the very topic being security, firms are reluctant to disclose their choices of practices, their level, and performance implications because they do not want others (especially offenders) to know what actions/practices they undertake and they do not want to suffer any adverse effects on their insurance premiums, reputation, and public image. Despite the continuous call for more empirical validation (Williams et al., ; Cigolini, Pero, & Sianesi, ), the effect of security related practices on security performance is still understudied (Williams, Lueg, Goffnett, LeMay, & Cook, ; Ni, Melnyk, Ritchie, & Flynn, ). Similarly, Hu, Hart, and Cooke () state that one of the major hurdles in conducting empirical research on information systems security “is acquiring access to organizations and individuals who are willing to discuss information which is understandably sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…However, given the very topic being security, firms are reluctant to disclose their choices of practices, their level, and performance implications because they do not want others (especially offenders) to know what actions/practices they undertake and they do not want to suffer any adverse effects on their insurance premiums, reputation, and public image. Despite the continuous call for more empirical validation (Williams et al., ; Cigolini, Pero, & Sianesi, ), the effect of security related practices on security performance is still understudied (Williams, Lueg, Goffnett, LeMay, & Cook, ; Ni, Melnyk, Ritchie, & Flynn, ). Similarly, Hu, Hart, and Cooke () state that one of the major hurdles in conducting empirical research on information systems security “is acquiring access to organizations and individuals who are willing to discuss information which is understandably sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the above-mentioned statements, Ni et al (2016) found that the primary motivation of early adopters of the C-TPAT program was loss aversion, that is, the need to minimize the potential cost of failing to fulfill the criteria of a secure supply chain. Afterward adopters, in turn, were rather motivated by economic benefits resulting from possible cost reductions.…”
Section: The Role Of the Authorized Economic Operator Program In Enhancing Securitymentioning
confidence: 65%
“…Other risks that appear in global supply chains are security or compliance risks (Khan and Burnes 2007;Ni et al 2016). Customs administrations need to ensure the safety and security of countries by verifying the content of the shipments against the export and import declarations submitted by shippers.…”
Section: Risks In Maritime Shipmentsmentioning
confidence: 99%